Pengaruh Model Pembelajaran Kontekstual Terhadap Hasil Belajar Siswa Kelas Ii Pada Subtema Hidup Bersih Dan Sehat Di Rumah Di SD Negeri 124405 Pematang Siantar - Nabila Sekar Ayu; Andriono Manalu (JOURNAL SAINS STUDENT RESEARCH, 2023)
. This research aims to determine the effect of the contextual learning model on the learning outcomes of class II students on the sub-theme of clean and healthy living at home at SD Negeri 124405 Pematang Siantar odd semester FY 2023/2024. The type of research in this research is quantitative research. The research population was all class II A students at SD Negeri 124405 Pematang Siantar totaling 22 students. The sampling technique in this research is non-probability sampling, where the sample selected is a saturated sample. The sample in this study consisted of class II at state elementary school 124405 Pematang Siantar, totaling 22 students. The results of this research show that student learning outcomes using the contextual learning model are an average of 84.32%. The results of the t distribution test are at a significant level (ɑ = 0.05) and dk = N-1 = 22-1 = 21, namely tcount>ttable, so the data has a t distribution with results of 14.36>ttable 0.404. The data can be said to have a significant influence. The results of the t-test table prove that there is an influence of the contextual learning model (X) on learning outcomes (Y) with the result tcount 14.36 > ttable 0.404. This proves that there is a significant influence from the use of contextual learning models on the learning outcomes of class II students in the sub-theme of clean and healthy living at home at SD Negeri 124405 Pematang Siantar.